Factors That Influence Human Milk Feeding at Hospital Discharge for Preterm Infants in a Tertiary Neonatal Care Center in Taiwan. Issue 2 (April 2018) - Pai, Chia-Ming; Jim, Wai-Tim; Lin, Hsiang-Yu; Hsu, Chyong-Hsin; Kao, Hsin-An; Hung, Han-Yang; Peng, Chun-Chih; Chang, Jui-Hsing
Abstract : Human milk is considered optimal nutrition for newborn infants, especially preterm infants, and it can lessen morbidity in this population. Human milk feeding at hospital discharge may encourage breastfeeding at home. This study evaluated the incidence and predictive factors of human milk feeding of preterm infants at discharge. It included all preterm infants with gestational age of less than 37 weeks who were admitted to the Mackay Memorial Hospital in Taiwan from January to December 2010 who survived to discharge. Infants were classified into a human milk group or a formula milk group. Gestational age, birth weight, length of hospital stay, maternal age, maternal educational status, and morbidity of prematurity were compared between the groups. Of the 290 preterm infants, 153 (52.8%) were being fed human milk at hospital discharge. Compared with the formula milk group, the human milk group had lower birth weights, younger gestational age, higher rates of ventilator use, and longer hospital stays. These differences were not statistically significant for very low-birth-weight (birth weight of <1500 g) infants ( n = 66). Multivariate analysis indicated that 2 factors, longer hospital stay and neonatal intensive care unit admission, were associated with human milk feeding at hospital discharge. These findings highlight the need for encouraging and helping all mothers, even those with relatively mature and healthy infants, to provide human milk for their infants.